Влияние неблагоприятных метеорологических условий на зимнюю орнитофауну Ашхабада и его окрестностей - Смогоржевский, Л.А. (Вестник зоологии, 1972)
During every day excursions in the visinity of Ashkhabad in winter 1968/1969 it was established that severe meteorological conditions influence negatively a number of birds.
Syrrhaptes paradoxus P a l l., Oenanthe lugens L i c t, Serinus pusillus P a l l., G a l e r i d a c r i s t a t a L. died. The birds appeared which were not seen here before - Phoenicurus erythronotus E v e r s m. and Prunellidae.